Analisis Struktur Lagu Bendera Ciptaan Eross Candra - Rafli, Fajri; Ayuthia Mayang Sari; Jagar Lumbantoruan (Universitas Negeri Padang, 2024)
This research aims to analyze the song structure used in the song Bendera. This research method is a qualitative method with a systematic content analysis approach, objectivity and generalization. Data collection techniques through literature study and laboratory work. Data analysis techniques are carried out from the stages of listening to recordings, playing melodies, transcribing songs, analyzing song structures, describing and drawing conclusions. Based on the research results, it can be concluded that the song Bendera shows that the structure of the song is a song with a three-part form (A-B-C) which is a development in the form of a period (A-B-B'-Bridge-C-C1). There are four basic rhythmic motifs and melodic motifs that make up the song Bendera, there are 9 types, namely m, n, o, p, q, r, s, t and u which are then developed by processing the motifs so that 10 types of motifs emerge, namely n1, o1, o2 , o3, r1, s1, t1, u1, u2, and u3. There are 11 phrases in the Bendera song, including five antecedent phrases and six consequent phrases. Cadences found in the Bendera song include perfect cadences, half cadences, half plagal cadences and deviant cadences. The lyrics and melody in the song Bendera are filled in a neumatic form where each word is filled with several notes.